2018
DOI: 10.1111/codi.14237
|View full text |Cite
|
Sign up to set email alerts
|

Resection with primary anastomosis vs nonrestorative resection for perforated diverticulitis with peritonitis: a systematic review and meta‐analysis

Abstract: This meta-analysis found that organ/space SSI rates as well as ostomy nonreversal rates were decreased in PRA at the cost of prolonging the operating time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 52 publications
2
24
0
1
Order By: Relevance
“…2 Quantitative analyses of a short-term mortality rates in randomized controlled trials, b long-term mortality rates in randomized controlled trials, and c overall mortality rates during follow-up in observational studies the present study, no difference between treatment groups was demonstrated, which is comparable to the outcomes found by Acuna et al [36]. Furthermore, Acuna et al [36] and Gachabayov et al [34] both demonstrated PA patients to be more likely to undergo stoma reversal and be stoma free during follow-up, which is similar to the present results. Recently, two population-based analyses of patients who underwent emergency surgery for acute diverticulitis in the USA were published by Lee et al [37] and Gawlick et al [38].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…2 Quantitative analyses of a short-term mortality rates in randomized controlled trials, b long-term mortality rates in randomized controlled trials, and c overall mortality rates during follow-up in observational studies the present study, no difference between treatment groups was demonstrated, which is comparable to the outcomes found by Acuna et al [36]. Furthermore, Acuna et al [36] and Gachabayov et al [34] both demonstrated PA patients to be more likely to undergo stoma reversal and be stoma free during follow-up, which is similar to the present results. Recently, two population-based analyses of patients who underwent emergency surgery for acute diverticulitis in the USA were published by Lee et al [37] and Gawlick et al [38].…”
Section: Discussionsupporting
confidence: 84%
“…The present results are generally in line with those from previous meta-analyses. With regard to overall mortality from randomized and observational studies, Gachabayov et al [34] and Shaban et al [35] found PA to be favorable over HP, which was also the case in the present quantitative analysis of mortality within the included observational studies. However, in the subgroup analysis of randomized studies in a b c Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Resection with primary anastomosis vs nonrestorative resection for perforated diverticulitis with peritonitis: a systematic review and metaanalysis by Gachabayov M et al 1 Gachabayov M et al [1] present a systematic review on the ongoing hot topic-how to operate on perforated diverticulitis? The primary endpoint of this systematic review was postoperative mortality including overall mortality, mortality after emergency surgery and mortality after ostomy reversal.…”
Section: Editor's Choicementioning
confidence: 99%
“…In recent years, results have been published favouring sigmoidectomy with primary anastomosis (PA) over Hartmann's procedure (HP) for the treatment of Hinchey III and IV diverticulitis 8 . Benefits of PA comprise lower short-term morbidity rates after index and reversal procedures, as well as a higher rate of stoma-free survival, including details of cost analyses and clinical outcomes, has been reported previously 11,12 .…”
Section: Introductionmentioning
confidence: 99%